INVESTIGATING CHANGES IN CELL CYCLE DISTRIBUTION OF CULTURED CELLS IN RESPONSE TO MICROTUBULE INHIBITORS - Ten, Marina (Nazarbayev University School of Sciences and Humanities, 2022)
Microtubules participate in the separation of chromosomes during mitosis. Microtubule (MT) inhibitors preclude normal cell division by interfering with mitotic spindle formation during anaphase. Failure to form a mitotic spindle for a prolonged time results in prolonged mitotic arrest. The arrest in mitosis can be assessed via microscopy, where cell death in mitosis, cell survival via mitotic slippage, or unequal division outcomes can be directly observed. Different outcomes of mitotic arrest can also be analyzed at the populational level by measuring the DNA content of each cell in a population using flow cytometry. This method uses information on cell ploidy to draw a DNA content histogram, which represents the distribution of cells across different phases of the cell cycle. The normal distribution is depicted as a linear diagram of cycle phases, with the majority of cells in G0/G1 (2n), some in S (2n–4n), and others accumulating in G2/M (4n). As a result of mitotic arrest, normal cell cycle distribution changes. Microtubule inhibitors induce prevalent accumulation in G2/M or SubG1 populations. SubG1 or "sub-diploid" population have cells with <2n ploidy. It therefore represents hypodiploid or degraded DNA cells. In the SubG1 population, cells in late apoptosis with active nucleases and cells exited via unequal division (1n) can be obtained. G2/M population cells (4n) probably indicate cells that exited from the mitotic block without division (mitotically slipped cells). Spindle assembly checkpoint (SAC) is the cell's surveillance system during mitosis. Inability to satisfy its conditions leads to the mitotic block, as in the case with MT drugs. However, with the ability to deactivate SAC, the duration of mitotic arrest can be controlled. The duration of mitotic arrest may play a significant role in the cell's response to the treatment. Deactivation of SAC using an Aurora B kinase inhibitor (Barasertib) should theoretically result in reduced death signals, nuclear envelope re-formation even in cells with 4n set, and thus result in greater cell survival. Mitotically slipped cells can also be regarded as survived cells. Thus, G2/M-prone cell lines that produce them should be somehow sensitized. One way to sensitize cells (enhance apoptotic response) to MT treatment- is to force cells blocked in mitosis to die. It can be achieved with the inhibition of different anti-apoptotic BCL-2 proteins (BCL-2, BCL-XL, MCL-1). Shifting equilibrium towards cell death signals should enhance caspase-dependent apoptosis, and force mitotically slipped cells to die. In this work, we attempted to investigate the changes in cell cycle distribution that resulted from prolonged mitotic arrest in a dose-dependent manner. We tried to identify whether cell response was dependent on the nature of the mitotic inhibitor or, more probably, cell line dependent. It was obtained that all drugs exhibit similar effects within a cell line, but the inter-line response to drugs was highly variable. We found two types of responses to MT treatment: SubG1-prone and G2/M-prone accumulation of cells. In response to prolonged mitotic arrest, A549 and PC-3 cells showed accumulation in the G2/M peak, whereas HaCaT and HeLa cells accumulated in the SubG1 peak instead. We identified maximal and minimal drug threshold concentrations, which successfully describe the changes in cycle distribution that resulted from MT treatment. We discovered that inducing short mitotic blocks with an Aurora B kinase inhibitor probably plays a role in cell survival, forcing SubG1-prone cell lines to shift to G2/M-prone with many polyploid cells. We found that maintaining the level of anti-apoptotic BCL-XL proteins but not BCL-2 or MCL-1 proteins can affect the shift of G2/M-prone cells to become SubG1-prone.
Keywords: Type of access: Open Access